The Unbearable Lightness of Reductionist Physicalism in Contemporary Psychiatry - (:unkn) unknown (AVES, 2020)
Being one of the most renowned subjects in philosophy, mind-body problem focuses on the relationship between physical and mental phenomena. Various approaches have been developed throughout history with two perspectives having been the most prominent: the claim that mind is of material nature (physicalism) and that mind is radically separate from physical existence (dualism). With its core premises, mind-body problem and different approaches to it are crucially relevant for psychiatry. Psychiatry, in its daily practice and theory, is situated right at the site of this so-called mind-body gap. Psychiatrists' conceptualization of mind-body problem is deeply related not only to their views on the nature of subjectivity and free will; but also to their implicit and explicit assumptions about psychopathology. In this mind-body problem framework, physicality is mostly attributed to the nervous system, more specifically to the brain. Advances in genetics, molecular biology, cognitive science, psychopharmacology and brain imaging techniques have led neuroscientific paradigm to be the de facto conceptual framework for understanding mental activity and psychic experience. In this view, as with the rest of all psychological phenomena, mental disorders are also brain disorders and physical (i.e. reductionist) methods are key to understand, prevent, and treat these conditions. With the advent of neuroscience, biological approaches to psychopathology have also paved the way for the birth of a popular neuro-culture that shadow other approaches to psychopathology. Explaining complex phenomena through neurobiological substrates has paralleled the acceptance of a popular motto that can be summarized as you are your brain. Despite all expectations, diverted resources, and intellectual interest, neurobiological reductionism has yet to bring about the anticipated breakthrough in clinical practice of psychiatry. In this article, we aim to provide a brief overview of the mind-body problem, describe various aspects of neurobiological reductionism, and address its theoretical impasses and implications for psychiatry.
Keywords: reductionism; physicalism; mind-body; psychiatry; NEUROSCIENCE; MIND; FUTURE